Developing Potential Natural Resources and Human Resources Among The COVID-19 Pandemic in Gempolpendowo Village - Ratna Handayati; Muhamad Rifa’i; Muhammad Arif Rahmanto (Institute of Computer Science (IOCS), 2021)
This study aims to determine the development of Developing the Potential of Natural Resources and Human Resources in the Middle of the Covid-19 Pandemic in Gempolpendowo Village, Glagah District, and to determine the business development strategy. The data analysis method used is 1) qualitative descriptive analysis to find an overview of the freshwater fish cracker business strategy, 2) SWOT analysis to identify internal and external factors that are the strengths, weaknesses, opportunities and threats in the development of freshwater fish cracker business. Based on the results of the research in the discussion, it can be concluded that the PKK group of women is one of the groups of mothers in Gempolpendowo Village, Glagah District, who carry out a snack business made from freshwater fish, all of whose members consist of women - housewives. which is in the village of Gempol Pendowo. Based on the results of the research from the SWOT analysis, the calculation of the value that exists between strength (streght) and weakness (weaknes), opportunity (opportunity) and threat (treath), where the strength value is 1.70 while the weakness value is 1.21 thus there is a difference in value + 0.49, while the opportunity value is 1.71 and the threat value is 1.24 with a difference in value + 0.47. From the difference, a line can be drawn from the X and Y axes, and a point is found in the area of ​​strength (S) and opportunity (O), which allows an alternative aggressive strategy (SO) where this coordinate is in quadrant 1 (aggressive) This means that the Freshwater Fish Crackers Business has excellent strengths and opportunities, which can take advantage of the existing strengths and opportunities to develop Freshwater Fish Crackers.